Leveraging Linked Open Data: A Link Maintenance Framework - Regino, André Gomes; Reis, Julio Cesar dos (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2022)
Connections among RDF (Resource Description Framework) data elements represent the core of LOD (Linked Open Data). These connections are built with semi-automatic linking algorithms using a variety of similarity methods. Interconnected data demand automatic methods to maintain their consistency. Constant update of RDF connections is relevant for the evolution of RDF datasets. However, changing operations can influence well-formed links, which turns difficult the consistency of the connections over time. This study investigated new methods responsible for fixing and updating links among structured data following ontologies rules and properties. We contribute with the design and development of an automatic method that updates RDF links based on changing operations in RDF datasets. The framework that implements our method - named LODMF - was evaluated in terms of discovering broken links in big and well-known Linked Open datasets.